2014
DOI: 10.1016/j.ijdevneu.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Social‐cognitive, physiological, and neural mechanisms underlying emotion regulation impairments: understanding anxiety in autism spectrum disorder

Abstract: Anxiety is one of the most common clinical problems among children, adolescents, and adults with autism spectrum disorder (ASD), yet we know little about its etiology in the context of ASD. We posit that emotion regulation (ER) impairments are a risk factor for anxiety in ASD. Specifically, we propose that one reason why anxiety disorders are so frequently comorbid with ASD is because ER impairments are ubiquitous to ASD, stemming from socio-cognitive, physiological, and neurological processes related to impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
2
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(148 citation statements)
references
References 238 publications
(297 reference statements)
7
133
2
6
Order By: Relevance
“…There were examples of both types of RRB being used as a coping strategy for anxiety, which supports previous findings that anxiety may act as a motivator or trigger for RRB and that the behaviours are used as a coping strategy (Joosten et al, 2009;Rodgers, Glod, et al, 2012). Related to this, the idea that anxiety in ASD may be related to poor emotional regulation (White et al, 2014) is potentially supported by findings from the interviews where young people talked about RRB in terms of a way to feel calm and reduce anxious feelings.…”
Section: Discussionsupporting
confidence: 84%
“…There were examples of both types of RRB being used as a coping strategy for anxiety, which supports previous findings that anxiety may act as a motivator or trigger for RRB and that the behaviours are used as a coping strategy (Joosten et al, 2009;Rodgers, Glod, et al, 2012). Related to this, the idea that anxiety in ASD may be related to poor emotional regulation (White et al, 2014) is potentially supported by findings from the interviews where young people talked about RRB in terms of a way to feel calm and reduce anxious feelings.…”
Section: Discussionsupporting
confidence: 84%
“…In a study of emotion regulation strategies, Mazefsky et al [35▪] found that adolescents with high-functioning ASD were more likely to use maladaptive and involuntary emotion regulation skills (e.g., rumination, increased arousal, shutting down) compared with typically developing controls. White et al [36▪] recently published an extensive review that parsed out the various sociocognitive, physiological, and neurobiological mechanisms that moderate the relationship between emotion regulation deficits and anxiety. The authors proposed a developmental model linking ASD, emotion dysregulation, and anxiety.…”
Section: Risk Factors and Correlates Of Anxiety In Autism Spectrum DImentioning
confidence: 99%
“…Indeed, people with anxiety-related disorders have been found to have heightened physiological responses to mutual eye contact (Wieser et al 2009), and they tend to avoid or fear mutual eye contact (Roelofs et al 2010;Schulze et al 2013). Internalising symptoms, such as anxiety are so prevalent in ASD that Mazefsky and colleagues have argued that a higher risk for anxiety is intrinsic to the disorder, stemming from commonly co-occurring emotion regulation impairments (Mazefsky et al 2012(Mazefsky et al , 2013Mazefsky and Herrington 2014;White et al 2014). Indeed Corden et al (2008) found that reduced visual attention to the eyes in adults with ASD was related their levels of social anxiety (however, the study did not examine response to mutual vs. non-mutual gaze).…”
Section: Emotional Arousal To Mutual Gazementioning
confidence: 99%
“…Third, following the initial findings of Corden et al (2008), we expected an association between less visual attention to eye region and more internalising symptoms in the ASD group. Fourth, based on the theoretical model outlined by Mazefsky and colleagues, (Mazefsky et al 2012(Mazefsky et al , 2013Mazefsky and Herrington 2014;White et al 2014), we predicted that emotional arousal to mutual gaze in ASD, a potential measure of emotional dysregulation, would relate to internalising symptoms in this group. Based on the findings presented above, we also expected that children in the TD group would look more and have increased pupil dilation to mutual gaze relative to averted gaze, and greater pupil dilation to unfamiliar compared to familiar people.…”
Section: The Current Studymentioning
confidence: 99%